Tata Kelola Pembinaan di Lentera Tari Prodi Pendidikan Seni Pertunjukan FKIP Universitas Lambung Mangkurat - Permata Kumala Sari, Putri Yunita; Hartono, H; Syakir, S (Jurnal Tata Kelola Pendidikan, 2023)
'Lentera Tari' is one of the UKM (Student Activity Units) which is part of the 'Lentera Seni Performing' and is under the management of the Student Association (Hima) of Performing Arts Education FKIP, Lambung Mangkurat University. UKM which is owned by the Performing Arts Education Study Program FKIP ULM was formed as an effort to develop the potential of student specialization. The research method used is qualitative to capture existing phenomena and describe them concretely. This SME development system uses a governance approach from George R. Terry, who suggests the basic function of governance as a dynamic process which includes planning, organizing, actuating, monitoring or evaluation functions. In the management of 'Lentera Tari', the results obtained include: 1) the planning process in the weekly, semi-annual and incidental coaching agenda; 2) in organizing in the form of division of jobdesk fields and responsibilities of each; 3) in the process of movement in the form of the travel process of all members of the 'Lentera Tari' in coaching activities, coordination of performances and all work programs that have been planned and determined together; 4) at the monitoring stage is through evaluation for the members of the 'Lentera Tari' after each routine training material is finished, both knowledge of the text and context, with the aim of knowing the absorption of coaching, then evaluating to discuss the obstacles encountered during the coaching process, in order to strive for activities in accordance with predetermined plan.